The Role of Guidance and Counseling Teachers in Increasing Learning Motivation of Grade X Students of Mass Safinatunnajah Salura - Sahara, Ainun (Journal of Educational Studies, 2024)
This research is based on the results of observations and experiences of researchers, that at MAS Safinatunnajah Salura there are still many students who do not have the motivation to study at home or at school. The purpose of the researcher was to determine the efforts of BK teachers in increasing the learning motivation of MAS Safinatunnajah salura students. Low learning motivation is a problem experienced by students in their learning activities, factors that affect student learning motivation are because parents are busy working so that students become less attentive, when explaining lessons subject teachers do not provide learning techniques that provoke students and weak student learning motivation from within themselves. This study was conducted on grade X students Mas safinatun jannah salura.who experienced low learning motivation(Riyanti, 2019).